Life Cycle Assessment of Land-Use-Related Biodiversity Impacts from Feed Production in Pork Sector - Vilensten,Theodor (2025)
Global biodiversity is heavily damaged by human interventions. There are multiple drivers for human-caused biodiversity loss; however, land use linked to agricultural production is the leading one. In response to this major threat, the interest in and importance of assessing the potential biodiversity impacts, particularly those related to land use, have grown significantly. Especially within frameworks like life cycle assessment (LCA). A plethora of assessment methods have been developed. One of the most prominent methods was developed by Laura Schere, her method that includes species fragmentation and varying intensity levels of exploitation. This bachelor’s work will therefore apply Schere’s method on inventory on three pork feed blends. Obtained from an master thesis published in 2022. The data has already been analyzed using previous methods; applying Scherer's method will allow for an evaluation of how the results may differ. An ecoregion, distinct geographical areas containing similar communities and species, approach was used for this thesis. When applying Schere’s method, the total PDF for all three blends was similar, both for global and regional RSL when compared to the results using Chaudhary’s method presented in the master thesis .The impacts between the three blends remained consistent, indicating that the relative biodiversity impacts did not change with Scherer’s method. This results in similar recommendations. An optimization was also performed on the blends, where the ecoregions with the lowest characterization factors (CFs) were selected for each ingredient to minimize biodiversity impacts as much as possible, based on the ecoregions included in the inventory. As a result, the total decrease in Potentially Disappeared Fraction (PDF) ranged between 23–31%. For future studies, access to a larger number of ecoregions would allow for more precise and greater optimization. However, due to the data-intensive nature of LCA, such detailed input was difficult to obtain in this study. A greater pool of ecoregions would allow for better identification of impact hotspots and more targeted improvements in feed composition. To improve access to useful data, this paper suggests broader collaboration between academia, farmers, and food producers to enable more accurate and relevant assessments.